Tecendo uma cidade modelar: relações entre currículo, educação escolar e projeto da cidade de Curitiba na década de 1990 - Ferreira, Valeria Milena Röhrich (2008)
This research started from the fact that Curitiba has a city project which was explicitly developed in the 1990s engaging for its strength several groups from different fields, including the educational one. Thus, we aimed to answer the following question: how was the city project built and where can we place the school education in the relationships involved? Considering the school education, the emphasis was on the analysis of the actions of the Municipal Department of Education concerning the official curricular proposition and materials produced trying to strengthen and disseminate the city project in schools in the 1990s. As methodological procedures in order to characterize this project and understand its roots (with issues that date back to at least 70 years) and the way it is articulated to the spatial organization of Curitiba and to the representations which appear in different kinds of production, we selected data related to different fields (Urbanism, Architecture, Environment, Literature, Politics, Education, History and Geography), considering the existence of established voices and outsiders based on Elias s distinction. It was evidenced thus that the official voices that produced and spread the project s ideas created cohesion around them ensuring their success through the development of well performed speeches and great symbolic appeal, while the outsiders, because of the type of criticism which was diffused, were unable to achieve a better position in the scene of Curitiba. With respect to the curriculum and to the educational proposition current in the municipal education in the 1990s, we analyzed: one of the versions of the Basic Curriculum from the beginning of the 1990s, one of the versions of the Curricular Guidelines at the end of the 1990s, the Annual Municipal Reports from 1994 to 2004 (considering the education), some Pedagogical Projects of Schools, specifically with respect to developed themes and projects (37 projects), a volume of each series of the collection of textbooks called Lições Curitibanas Lessons of Curitiba (1994-95), the newspaper Curitibinha Little Curitiba (1996-2000) and various projects that were developed in schools at the end of the 1990s, also examining the speeches present at the press about the mayors who were in charge of the city (Lerner: 1971-74, 1979-82,1989-92) and the speeches about the ones in charge in the present period: Rafael Greca (1993-1996) and Cássio Taniguchi (1997-2004). This analysis had as a reference Bourdieu s understanding about the social world and, with respect to curricular issues, Gimeno Sacristán s and Giroux s works, allowing us to notice the importance given to the school education in order to compose and disseminate such project in the management of the mayors listed above, but with significant differences concerning the educational proposals. In the first case, the emphasis was given to the production of materials, notably Lições Curitibanas, the newspaper Curitibinha (given to each child of the public schools) and initiatives aiming the cultural expansion, for example, Faróis do Saber (The headlights of knowledge), Ceis (Centers of Integral Education of Curitiba) and projects such as music, theater, School Radio. In the second case, the emphasis was on the development of the environmental program Alfabetização Ecológica ("Ecological Literacy"), the Curricular Guidelines and partnerships with strong liberal tendencies (NGOs, companies, amigos da escola school friends ). Overall, we can say that the official curriculum of the municipal education in the 1990s offered the school a conservative analysis of the city, acting in order to strengthen and encourage the nonpolitical citizen, trying to frame him to the image of a model city correct , ecological , with an ideal planning and with the union of ethnic groups - in which social and racial inequalities are relegated to a low level or to the invisibility